Artificial Insemination in Queens in the Clinical Practice Setting: Protocols and challenges. Issue 9 (September 2022) - Zambelli, Daniele; Cunto, Marco
Practical relevance: Despite substantial advances in assisted reproductive techniques having been recently reported in cats, the use of these is limited and routine application is still far from being a reality in veterinary clinics. Nevertheless, there is an increasing demand from domestic cat breeders for artificial insemination (AI) techniques that are already commonly used in dogs. Where natural breeding is not possible in tom cats and queens of high breeding value, AI could offer a solution. Clinical challenges: AI in cats is more difficult than in other species – both in terms of semen collection/handling and oestrous cycle management given that ovulation must be induced. Aim: For practitioners wishing to perform AI in queens, there are challenges to overcome, and a good understanding of the techniques and procedures involved is pivotal. This review aims to contribute to improved knowledge by providing an overview of AI protocols, encompassing choice of breeding animals, procedures for semen collection, oestrus and ovulation induction, AI techniques and equipment. Equipment and technical skills: Depending on the animals involved and the specific AI technique chosen, essential equipment may include an artificial vagina, electroejaculator, endoscope (sialendoscope, which can be fairly expensive) and special catheters for transcervical insemination. Other instrumentation and materials needed are typically readily available in a veterinary clinic. In general, no particular skills are needed to perform the procedures described in this review, with the exception of endoscopic transcervical catheterisation, where the ability to use an endoscope is required. Evidence base: The information and advice/recommendations provided are based on specific feline research and reviews published in scientific peer-reviewed journals, animal reproduction textbooks, and presentations at national and international congresses. The authors also drew on their own clinical experience with regard to the choice of protocols and procedures presented in this review.